Pengembangan Media Interaktif Wordwall Pada Mata Pelajaran Matematika Materi Penjumlahan dan Pengurangan di Kelas 1 Sekolah Dasar - Hery, Setiyawan; Feri Hermawan; Arimbi Salma Bahira; Elsa Wahyu Ningrum; Maulana Rafi Rulis Saputra (PESHUM : Jurnal Pendidikan, Sosial dan Humaniora, 2025)
This study aims to develop an interactive learning media using Wordwall for teaching mathematics, specifically addition and subtraction, in first grade elementary school students. The research employed a research and development (R&D) method using the ADDIE model, wich includes analysis indicated the importance of engaging and interactive media to improve student’s motivation and understanding. The developed product was validated by subject metter, language and media expert, resulting in average scores of 85% and 92%, categorized as highly valid. The classroom implementation received positive responses from both teachers and students. Evaluation results showed a significant improvement in learning outcomes, with mastery increasing from 33.33% in the first cycle to 76.93% in the second cycle. This indicated that Wordwall media effectively helps student’s understanding basic mathematical concepts of addition and subtraction, enhances participation, and creates a more engaging learning environtment. Therefore, Wordwall is recommended as an innovatife and effective learning media to improve mathematics learning outcomes in elementary schools.